PENATALAKSANAAN NUTRISI UNTUK PASIEN COVID 19 DI RUMAH SAKIT BHAYANGKARA TK II MEDAN - Pasaribu, Dormaulina; Nababan, Donal; Sinaga, Janno; Ginting, Daniel; Sipayung, Rosetty; Sitorus, Mido Ester J. (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2023)
Nutrition management for COVID-19 patients at the hospital. Bhayangkara TK II Medan is not happy with the nutritional management guidelines for COVID-19 patients. Bhayangkara TK II Medan. The type of Ingkang Panaliten is supported by a high level of marriage with the qualitative Kanthi Panaliten with a phenomenological approach. Informant ing panliten iki dumadi saka key informant (key informant), main informant and informant of triangulation/additional cacah 9 wong. Data collection through interviews/direct interviews with informants and the results of the Panliten Nuduhake on nutritional management of COVID-19 patients in hospitals. Bhayangkara TK II Medan adhedhasar needs energy, macronutrients, micronutrients and isotonic requirements not in accordance with the COVID 19 nutritional management guidelines, and the management of electrolyte needs increases with the COVID 19 nutrition management guidelines. go to hospital. Bhayangkara TK II Medan is trying to take care of nutritional management for Covid patients with the guidelines for nutritional management for Covid patients, preventing the immunity of Covid 19 patients from dropping and taking the healing process to the hospital for Covid 19 patients. Bhayangkara Kindergarten II Medan Kanggo adds to the nutritional needs of independent Kanthi, Saliyane Kanggo, to meet the nutritional needs of Saliyane Sing Wis, visited the hospital. Bhayangkara TK II Medan so that the immunity of COVID-19 patients is reduced and the healing process takes place.